2016
DOI: 10.4236/nm.2016.72008
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Burnout Theory of Chronic Fatigue Syndrome

Abstract: There is no agreement on the etiology of chronic fatigue syndrome (CFS), and the main theories (behavioural and viral/immune) do not satisfactorily explain the condition. A growing body of evidence suggests that CFS may be caused by a dysfunction of the stress system-and the hypothalamic-pituitary-adrenal (HPA) axis in particular-as a result of chronic stress. CFS shares many similarities to occupational burnout, including similar symptoms, physiological abnormalities and triggers. After a brief review of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…24 Several theories implicate the body's stress hormonal systems as the basis of CFS/ME; it has been suggested for example that the condition arises from the same physiological processes as those that occur in 'burnout'. 25 It could therefore be hypothesised that the improvement in well-being found in this study could lead to a reduction in fatigue in the long term. This requires further research.…”
Section: Directions For Future Researchmentioning
confidence: 80%
“…24 Several theories implicate the body's stress hormonal systems as the basis of CFS/ME; it has been suggested for example that the condition arises from the same physiological processes as those that occur in 'burnout'. 25 It could therefore be hypothesised that the improvement in well-being found in this study could lead to a reduction in fatigue in the long term. This requires further research.…”
Section: Directions For Future Researchmentioning
confidence: 80%
“…Chronic fatigue syndrome (CFS) is characterized by persistent crippling fatigue for 6 months or more, and usually leads to physical and cognitive difficulties [1–3] . The incidence of CFS in adults is between 0.007% and 2.8%, and it is higher in women, about 4 times higher than in men [4] . It is reported that an estimated 836,000 and 2.5 million Americans suffer from CFS, and the unemployment rate of patients with CFS is between 35% and 69%, and the loss of personal income of patients’ families is about $20,000 a year, causing serious economic losses [5] .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The incidence of CFS in adults is between 0.007% and 2.8%, and it is higher in women, about 4 times higher than in men. [4] It is reported that an estimated 836,000 and 2.5 million Americans suffer from CFS, and the unemployment rate of patients with CFS is between 35% and 69%, and the loss of personal income of patients' families is about $20,000 a year, causing serious economic losses. [5] The incidence rate of CFS in China is up to 5.58%.…”
Section: Introductionmentioning
confidence: 99%